Full‐length sequence of the novel HLA‐B40:537 allele by next‐generation sequencing in a Chinese individual - Zhong, Xian‐xin; Quan, Zhan‐rou; Luo, Sheng‐hua; Yuan, Rui; Song, Lin‐li (HLA, 2023)
One nucleotide substitution in codon 116 of HLA‐B*40:06:01:12 results in a novel allele, HLA‐B*40:537.